Dental Phenotypes and Parental Perspective of Quality of Life for Patients with Ectodermal Dysplasia and Isolated Hypodontia - CROSSAN, EMILY (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2020)
Dental Phenotypes and Parental Perspective of Quality of Life for Patients with Ectodermal Dysplasia and Isolated Hypodontia. Crossan E, O Connell AC, (Dublin Dental University Hospital, Trinity College Dublin, Ireland) Aim: This study aimed to compare the parental perspectives on OHRQoL impact and dental experience for children with ectodermal dysplasia (ED), severe isolated hypodontia (IH), and age and gender matched controls; and to identify distinctive features to differentiate between IH and ED. Method: A cross-sectional study of 172 children (mean age: 12.4-years old); 86 (29 children with ED and 57 children with IH) with severe hypodontia (> 6 missing teeth) and 86 age and gender matched controls were recruited from the Dublin Dental University Hospital. The Parental-Caregiver Perceptions Questionnaire (P-CPQ), global rating, Family Impact Scale (FIS) and a specifically designed questionnaire were used to gather information on parental perceptions of OHRQoL and dental experiences, respectively. Clinical examinations were used to identify missing teeth and any dental abnormalities. Results: There were statistically significant differences (p<0.05) in all global rating, P-CPQ and FIS scores for the ED cases and their matched controls. IH cases and their matched controls, had statistically significant differences in global rating, overall P-CPQ and in 2 P-CPQ domains; emotional and social well-being, and the overall FIS score, as well as for parental emotional well-being. The ED mean scores for functional limitations were significantly greater than the IH mean scores. P-CPQ scores for males with ED had a moderate correlation with functional limitations, oral symptoms and overall QoL. The ED group reported the highest perceived number of appointments ( 20 or more ; 58.6%). Parents from the ED and IH groups reported the main information deficits were related to treatment timing and lack of explanation of the condition itself. Conclusion: Parents of children with ED and IH perceive a significant impact on QoL, for both the child and their family. Clinicians need to be aware of the significant attendance burden and the need for good communication and more parental involvement in the treatment planning process.
APPROVED
Keywords: Quality of Life; Ectodermal Dysplasia; Isolated Hypodontia; P-CPQ; Parental Perspective of Quality of Life; FIS; Parental-Caregiver Perceptions Questionnaire; Family Impact Scale; Tooth Agenesis; Tooth Agenesis Code; Hypodontia; Oligodontia; Oral Health-Related Quality of Life; Congenitally missing teeth